(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
Studying the history of the church, especially its social fabric, the foundations of its economic development, the spiritual life and worldliness of the congregations, is one of the most complex issues in world history. There is a practice of reconstructing these historical periods based on stone-era monuments materials. From this point of view, in the following lines, we will draw on the sources obtained in the study of material culture of stone-age communities throughout Central Asia in the years to come, highlighting the social relationships and spiritual life of the times.